Kehidupan Gay dalam Perspektif Interaksionisme Simbolik - Bayu Irawati RM; Nur Hasyim (JSW (Jurnal Sosiologi Walisongo), 2019)
This study aims to explore gay life in Palembang using a symbolic interactionism perspective. The research applies a symbolic interactionism method to understand the behavior and social interaction of gays in their daily lives. Primary data is obtained through participatory observation and direct interviews using interview guidelines. While secondary data is gathered from many articles about homosexuals such as gay, lesbian, or LGBT. The results showed that first, gays have their own symbols both gesture and other communication types in their social lives such as in family life, intimate relationship, friendship, workplace, and in their neighborhood life. Second, gays define their sexual orientation as natural and consider themselves different from transsexuals since they do not transform their masculine identities.